2008
DOI: 10.1627/jpi.51.225
|View full text |Cite
|
Sign up to set email alerts
|

直留ナフサおよびfccガソリン中の硫黄化合物の分析

Abstract: Sulfur-containing compounds in straight-run naphtha and catalytic-cracked gasoline were analyzed quantitatively using gas chromatography with a sulfur chemiluminescence detector. Pretreatment of the samples by open column chromatography and silver nitrate treatment were introduced to assign sulfur species. Commercial reagents, prepared standard samples and a commercial mass spectrum library were also utilized to assign the sulfur species. The sulfur content of naphtha was 242 ppm and 83 compounds were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, from another perspective, the catalyst of Ni/ g-C 3 N 4 -T may be a potential sulfur-resistant material; after all, naphtha and its derived ethylene feeds generally consist of several hundred ppm of sulfide. 28 Another important issue is oligomerization. In fact, oligomerization and its corresponding oligomers are extremely complex, due to considerable species from C 3 to C 32 and from gas-phase to liquid-phase to solid-phase oligomers, including alkenes, dienes, and alkanes with series of isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from another perspective, the catalyst of Ni/ g-C 3 N 4 -T may be a potential sulfur-resistant material; after all, naphtha and its derived ethylene feeds generally consist of several hundred ppm of sulfide. 28 Another important issue is oligomerization. In fact, oligomerization and its corresponding oligomers are extremely complex, due to considerable species from C 3 to C 32 and from gas-phase to liquid-phase to solid-phase oligomers, including alkenes, dienes, and alkanes with series of isomers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is a problem to be solved. However, from another perspective, the catalyst of Ni/g-C 3 N 4 -T may be a potential sulfur-resistant material; after all, naphtha and its derived ethylene feeds generally consist of several hundred ppm of sulfide …”
Section: Resultsmentioning
confidence: 99%
“…Straight run naphthas have sulfur concentrations usually ranging from 20 to 100 ppmw, 2,11 although values as high as 250 ppmw can be reached. 62,63 It is thus obvious that the observations made for coking during ethane cracking cannot be simply translated to naphtha cracking. Hence, there is a clear need to study coke formation under naphtha cracking conditions on several alloys to determine if the material has an impact on coke formation during naphtha cracking as significant as during ethane cracking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that unsaturated and aromatic hydrocarbons have the highest coking tendency. , Therefore, typically a distinction is made between coking models developed for gaseous feeds , and liquid feeds. ,,, An additional complexity is the presence or addition of sulfur to the feed because this element typically increases coke formation, although it also causes a significant reduction of CO in the effluent stream. Straight run naphthas have sulfur concentrations usually ranging from 20 to 100 ppmw, , although values as high as 250 ppmw can be reached. , It is thus obvious that the observations made for coking during ethane cracking cannot be simply translated to naphtha cracking. Hence, there is a clear need to study coke formation under naphtha cracking conditions on several alloys to determine if the material has an impact on coke formation during naphtha cracking as significant as during ethane cracking.…”
Section: Introductionmentioning
confidence: 99%